Role of Export, Import and Gross Capital Formation in Iraq: A Granger Causality Approach - Abdulsahib, Ahmed Saddam (International Journal of Economics and Financial Issues, 2024)
This study aims to investigate the link amongst cointegrated observations of export, import and gross capital formation (GCF) in Iraq over the period 2004-2021. This study assumes that the high reliance on the crude oil revenues cannot lead to enhance level of economic diversification and stability. However, the main objective of this paper is to empirically analyse the relationship between export, import and gross capital formation. For this purpose, the study employs a granger causality test. It revealed a considerable linkage between the variables examined, in which a long-run unidirectional causal relationship is existed from GCF to export and import, and also from export to import. Whereas the causal link from export and import to GCF is absent. This implies that the sound economic policy in Iraq is not engaged efficiently due to the modest level of GCF impact, in which there is a parallel relationship between export and import in general, where the major export revenues devoted for meeting the consuming needs over the period studied. The study recommended gross capital formation in Iraq ought to be increased and utilized in efficient way that lead to raise level of value added, where this could be achieved via enhancing level of export, particularly non-oil export. Accordingly, it also recommended to attracting domestic and foreign investors.